Discordance between ICD-Coded Myocardial Infarction and Diagnosis according to the Universal Definition of Myocardial Infarction. (6th January 2020) - Díaz-Garzón, Jorge; Sandoval, Yader; Smith, Stephen W; Love, Sara; Schulz, Karen; Thordsen, Sarah E; Johnson, Benjamin K; Driver, Brian; Jacoby, Katherine; Carlson, Michelle D; Dodd, Kenneth W; Moore, Johanna; et al.
Abstract: BACKGROUND: International Classification of Diseases (ICD) coding is the standard diagnostic tool for healthcare management. At present, type 2 myocardial infarction (T2MI) classification by the Universal Definition of Myocardial Infarction (MI) remains ignored in the ICD system. We determined the concordance for the diagnosis of MI using ICD-9 coding vs the Universal Definition. METHODS: Cardiac troponin I (cTnI) was measured by both contemporary (cTnI) and high-sensitivity (hs-cTnI) assays in 1927 consecutive emergency department (ED) patients [Use of TROPonin In Acute coronary syndromes (UTROPIA) cohort] who had cTnI ordered on clinical indication. All patients were adjudicated using both contemporary and hs-cTnI assays. The Kappa index and McNemar test were used to assess concordance between ICD-9 code 410 and type 1 MI (T1MI) and type 2 MI (T2MI). RESULTS: Among the 249 adjudicated MIs using the contemporary cTnI, only 69 (28%) were ICD-coded MIs. Of 180 patients not ICD coded as MI, 34 (19%) were T1MI and 146 (81%) were T2MI. For the ICD-coded MIs, 79% were T1MI and 21% were T2MI. A fair Kappa index, 0.386, and a McNemar difference of 0.0892 ( P < 0.001) were found. Among the 207 adjudicated MIs using the hs-cTnI assay, 67 (32%) were ICD coded as MI. Of the 140 patients not ICD coded as MI, 27 (19%) were T1MI and 113 (81%) were T2MI. For the ICD-coded MIs, 85% were T1MI and 15% T2MI. A moderate Kappa index, 0.439, and a McNemar difference of 0.0674 ( P < 0.001) were found. CONCLUSIONS: ICD-9–coded MIs captured only a small proportion of adjudicated MIs, primarily from not coding T2MI. Our findings emphasize the need for an ICD code for T2MI.